The Comparison of Effects of Supplementation of Zeolite and Yucca Schidigera Powder to Diet on Liver Enzymes (AST, ALT, GGT) in Sheep - Oğuz Kale; İbrahim Durmuş (Turkish Journal of Agriculture: Food Science and Technology)
The concern of utilizing native coraps as forage supplements instead of antibiotics has increased in order to manipulate rumen fermentation.The purpose of current work was to determine effects of co-addition zeolites of and Yucca schidigera (YS) plant containing high level of saponin to sheep feed on plasma Aspartat aminotransferaz (AST), ALT (Alanin aminotransferaz) and Gama glutamil transferaz (GGT) levels. A total of 24 sheep wereusedas 6 of eachgroup. Sheepwas fed foronemonth as control, supplementedwithZeolite (3%), Yuccaschidigera (YS, 1500 ppm) and Zeolite (3%) + YS (1500 ppm) to basal diet. When trial finished, plasma AST, ALT and GGT levels were determined in blood samples taken from all groups. In the study, detected supplement of zeolite and YS did not have an impact on ALT and AST, whereas zeolite additions decreased GGT levels. As a result; zeolite and YS supplementation applied in this study did not have a negative impact liver welfare sheep.